2021
DOI: 10.1002/1878-0261.12967
|View full text |Cite
|
Sign up to set email alerts
|

SENP3 loss promotes M2 macrophage polarization and breast cancer progression

Abstract: Tumor-associated macrophages (TAMs) play a crucial role in promoting cancer progression. Upon cytokine stimulation, TAMs preferentially polarize to the anti-inflammatory and pro-tumor M2 subtype . The mechanism underlying such preferential polarization remains elusive. Here, we report that macrophage-specific deletion of the SUMO-specific protease SENP3 promotes macrophage polarization towards M2 in bone-marrow-derived macrophage (BMDM) induced by IL4/IL13 and in an ex vivo model (murine Py8119 cell line), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…SUMO also influences the activity of NF-κB signaling regulators, NEMO and IκBα, affecting immune response activation [158][159][160][161][162]. SENP3-mediated deSUMOylation regulates antitumor immune response functions of Tregs, macrophages, and dendritic cells [163][164][165]. The loss of SENP3 deSUMOylase activity in Tregs results in dysregulation T-cell homeostasis and SENP3 deficiency in macrophages facilitates macrophage polarization towards the pro-tumor M2 subtype.…”
Section: Sumoylation In Cellular Processes Relevant For Cancermentioning
confidence: 99%
“…SUMO also influences the activity of NF-κB signaling regulators, NEMO and IκBα, affecting immune response activation [158][159][160][161][162]. SENP3-mediated deSUMOylation regulates antitumor immune response functions of Tregs, macrophages, and dendritic cells [163][164][165]. The loss of SENP3 deSUMOylase activity in Tregs results in dysregulation T-cell homeostasis and SENP3 deficiency in macrophages facilitates macrophage polarization towards the pro-tumor M2 subtype.…”
Section: Sumoylation In Cellular Processes Relevant For Cancermentioning
confidence: 99%
“…In this study, we established FAI using the focal adhesion gene and found that it was closely related to M2 macrophage infiltration. M2 macrophage markers CD163 (Yamaguchi et al, 2016) and MRC1 (Xiao et al, 2021) were also observed to be significantly higher in the high FAI group than in the low FAI group. EMT signaling is a key factor for tumor resistance, regulation of angiogenesis, and promotion of growth (Sabbah et al, 2008;Banias et al, 2020).…”
Section: Discussionmentioning
confidence: 83%
“… 188 IFN‐γ induced by viral infection acted on Toll‐like receptor signaling in macrophages and initiated mitochondria‐driven cell death. 189 , 190 In this process, nitric oxide synthase was induced to promote caspase‐8 cleavage and activate mitochondrial apoptotic effectors. Importantly, the mitochondria‐driven apoptosis potentially increased disease severity in COVID‐19 patients.…”
Section: Mechanisms Of Remodeling Host Metabolism By Sars‐cov‐2mentioning
confidence: 99%